2018
DOI: 10.1016/j.jpag.2017.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Video Intervention to Increase Perceived Self-Efficacy for Condom Use in a Randomized Controlled Trial of Female Adolescents

Abstract: The Seventeen Days program shows promise to improve perceived self-efficacy to acquire condoms among sexually active female adolescents-an important precursor to behavior change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 44 publications
1
21
0
14
Order By: Relevance
“…These include low perceived sexual satisfaction derived from the use of condoms, low perceived personal risk of STDs, condom fatigue, having a steady sexual partner, and low condom self-efficacy [1113, 29, 30]. Studies have identified self-efficacy as the most important predictor of condom use [13, 3134]. Bandura [35] coined the term ‘self-efficacy’ and defines it as a “judgment of one’s capability to accomplish a certain level of performance”.…”
Section: Introductionmentioning
confidence: 99%
“…These include low perceived sexual satisfaction derived from the use of condoms, low perceived personal risk of STDs, condom fatigue, having a steady sexual partner, and low condom self-efficacy [1113, 29, 30]. Studies have identified self-efficacy as the most important predictor of condom use [13, 3134]. Bandura [35] coined the term ‘self-efficacy’ and defines it as a “judgment of one’s capability to accomplish a certain level of performance”.…”
Section: Introductionmentioning
confidence: 99%
“…Literature reported that self-efficacy is one of the most significant predictors of condom use. [14][15][16][17][18] According to social cognitive theory, self-efficacy is a central concept in which both outcome and efficacy of expectations are critical in the promotion of health and behavioral change. 19 Bandura 20 defines the term "self-efficacy" as a "judgment of one's capability to accomplish a certain level of performance".…”
Section: Introductionmentioning
confidence: 99%
“…Given that the majority of our sample only used one of the three female condoms provided, and did not have previous experience using the method nor saw a demonstration prior to use, participants’ experiences of inserting are likely to improve as they become more familiar with the method [ 25 , 30 ]. This could be facilitated by watching a demonstration online [ 31 , 32 ] or with the advice and support of a health professional [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%